“A theoretical framework of factors contributing towards the talent management practices and employee retention in contemporary organization” - et al., Priyanka Panday (International Journal of Advanced Science and Technology, 2019)
This Paper deals with an appraisal of the various dimensions of talent management practices contributing towards the retention of the employees in contemporary organization. The objective of the review is to present various dimensions related to talent management practices and it relation with employee retention. Various databases are used to review the literature; 121 research papers out of 430 are thoroughly discussed in the paper to assess the contemporary meaning and relationship of various dimensions of talent management leading to sustainability. Inclusion criteria of literature are the papers showing the relationship of at least two variables; rest all were excluded from the literature. The finding of the paper clearly identifies the strong positive relationship between these variables of talent management and employee retention and its direct positive relation to effectiveness of the organization was also clearly visible.